Introduction to communication systems - Madhow, Upamanyu (United Kingdom : Cambridge University Press, 2014)
An accessible undergraduate textbook introducing key fundamental principles behind modern communication systems, supported by exercises, software problems and lab exercises.
Part I. Introduction: 1.1 Analog or digital?; 1.2 A technology perspective; 1.3 The scope of this textbook; 1.4 Why study communication systems?; 1.5 Concept summary; 1.6 Notes; Part II. Signals and Systems: 2.1 Complex numbers; 2.2 Signals; 2.3 Linear time-invariant systems; 2.4 Fourier series; 2.5 The Fourier transform; 2.6 Energy spectral density and bandwidth; 2.7 Baseband and passband signals; 2.8 The structure of a passband signal; 2.9 Wireless-channel modeling in complex baseband; 2.10 Concept summary; 2.11 Notes; 2.12 Problems; Software labs; Part III. Analog Communication Techniques: 3.1 Terminology and notation; 3.2 Amplitude modulation; 3.3 Angle modulation; 3.3.1 Limiter-discriminator demodulation; 3.4 The superheterodyne receiver; 3.5 The phase-locked loop; 3.6 Some analog communication systems; 3.7 Concept summary; 3.8 Notes; 3.9 Problems; Software labs; Part IV. Digital Modulation: 4.1 Signal constellations; 4.2 Bandwidth occupancy; 4.3 Design for bandlimited channels; 4.4 Orthogonal and biorthogonal modulation; 4.5 Proofs of the Nyquist theorems; 4.6 Concept summary; 4.7 Notes; 4.8 Problems; Software lab; Appendices; Part V. Probability and Random Processes: 5.1 Probability basics; 5.2 Random variables; 5.3 Multiple random variables, or random vectors; 5.4 Functions of random variables; 5.5 Expectation; 5.6 Gaussian random variables; 5.7 Random processes; 5.8 Noise modeling; 5.9 Linear operations on random processes; 5.10 Concept summary; 5.11 Notes; 5.12 Problems; Appendices; Part VI. Optimal Demodulation: 6.1 Hypothesis testing; 6.2 Signal-space concepts; 6.3 Performance analysis of ML reception; 6.4 Bit error probability; 6.5 Link-budget analysis; 6.6 Concept summary; 6.7 Notes; 6.8 Problems; Software labs; Part VII. Channel Coding: 7.1 Motivation; 7.2 Model for channel coding; 7.3 Shannon's promise; 7.4 Introducing linear codes; 7.5 Soft decisions and belief propagation; 7.6 Concept summary; 7.7 Notes; 7.8 Problems; Part VIII. Dispersive Channels and MIMO: 8.1 The single-carrier system model; 8.2 Linear equalization; 8.3 Orthogonal frequency-division multiplexing; 8.4 MIMO; 8.5 Concept summary; 8.6 Notes; 8.7 Problems
Includes bibliographical references.
Keywords: TELECOMMUNICATION